Development and performance test of a separation system for removal of physically emulsified and free oils from wastewaters - Ngu, Lock Hei. (Universiti Malaysia Sarawak, UNIMAS, 2004)
A separation system with multiple angles parallel coalescence frustums was designed and experimental study was carried out to determine its efficiency in treating wastewaters loaded with physically emulsified and free oil droplets.